Electronic performance monitoring: The role of reactance, trust, and privacy concerns in predicting job satisfaction in the post-pandemic workplace - Nancy Brinson; Bahareh Amini; Laura Lemon; Claudia Bawole (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace)
Recent technological advancements combined with the accelerated trend toward remote work since the pandemic have contributed to a significant rise in electronic performance monitoring (EPM) in the workplace. Currently, nearly 80% of U.S. employers engage in some form of EPM to manage their employees. Using a theoretical foundation of Psychological Reactance Theory and the Stakeholders’ Privacy Calculus Model, this study examines employees’ perceptions of the risks and benefits associated with two common electronic monitoring practices (keyboard and video camera monitoring), and demonstrates how these factors influence employees’ privacy concerns, trust in their employer, and job satisfaction. Results from an online survey of 633 participants indicate that while employees appreciate the benefits of working remotely (and understand that EPM is a necessary component of it), they were also well aware of the risks associated with monitoring, including privacy invasion. Privacy concerns stemming from EPM were associated with a sizable reactance effect among respondents, which was, in turn, negatively correlated with both their attitude toward monitoring and their job satisfaction. That said, employer trust was strongly correlated with employees’ positive attitude toward monitoring, which exceeded the level of negative response associated with their reactance. Taken in tandem, these findings suggest that employees are weighing the perceived risks and benefits of monitoring as suggested by the Stakeholders’ Privacy Calculus Model in determining their reactance to EPM, their attitudes toward monitoring, and their job satisfaction.